2021
DOI: 10.1063/5.0058784
|View full text |Cite
|
Sign up to set email alerts
|

Interface-engineered barium magnetoplumbite–wide-bandgap semiconductor integration enabling 5G system-on-wafer solutions for full-duplexing phased arrays

Abstract: Transition from fourth to fifth generation wireless technologies requires a shift from 2.3 GHz to Ka-band with the promise of revolutionary increases in data handling capacity and transfer rates at greatly reduced latency among other benefits. A key enabling technology is the integration of Ka-band massive multiple input–multiple output (m-MIMO) antenna arrays. m-MIMO array elements simultaneously transmit and receive (STAR) data providing true full duplexing in time and frequency domains. STAR requires, as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…2 To this end, a central tenet of ongoing research is to demonstrate a viable path to the integration of ferrites with semiconductor platforms that are suitable for system-on-wafer (SoW) solutions that would enable Ka-band m-MIMO and ultimately the timely realization of 5G implementation. 4…”
Section: M R Smentioning
confidence: 99%
See 1 more Smart Citation
“…2 To this end, a central tenet of ongoing research is to demonstrate a viable path to the integration of ferrites with semiconductor platforms that are suitable for system-on-wafer (SoW) solutions that would enable Ka-band m-MIMO and ultimately the timely realization of 5G implementation. 4…”
Section: M R Smentioning
confidence: 99%
“…In 2021, Yu et al, 4 demonstrated the growth by PLD of BaM/ MgO/AlN/SiC(X) heterostructures. The use of single crystal SiC substrates made this research more relevant for industrial applications.…”
Section: Outlook: Ferrite-semiconductor Heterostructure Integrationmentioning
confidence: 99%
“…With the soaring development of the electronics industry in the past few decades, M-type hexagonal ferrites, which possess a magnetoplumbite structure, have been attracting a lot of attention and research. [1][2][3][4][5][6][7][8][9][10][11] O 19 ), which are widely used in microwave devices, permanent magnets, and magnetic recording media due to their large magnetocrystalline anisotropy along the c-axis, high coercivity, and saturation magnetization. 1 Microwave circulators based on garnet or spinel ferrites usually need a bias field provided by an external magnetic steel to operate normally.…”
Section: Introductionmentioning
confidence: 99%
“…With the soaring development of the electronics industry in the past few decades, M‐type hexagonal ferrites, which possess a magnetoplumbite structure, have been attracting a lot of attention and research 1–11 . M‐type hexaferrites have two representative materials, barium hexaferrite (BaM, BaFe 12 O 19 ) and strontium hexaferrite (SrM, SrFe 12 O 19 ), which are widely used in microwave devices, permanent magnets, and magnetic recording media due to their large magnetocrystalline anisotropy along the c ‐axis, high coercivity, and saturation magnetization 1 .…”
Section: Introductionmentioning
confidence: 99%